How Culture Gives the US an Innovation Edge Over China - Frey, Carl; Frey, Carl (MIT Sloan Management Review, 2021)
China's strong collectivist culture may have helped it to become a manufacturing powerhouse, but the individualistic United States may have an edge in technology-driven innovation.